Correlation of Plantation Area and Palm Oil Production in Sumatra and Kalimantan Regions - Kurniawan, Indra; Kurniadhi, Adhitya; Aji, Wandha Atmaka; Manto, Agus (Akademi Komunitas Perkebunan Yogyakarta, 2024)
This study aims to analyze the correlation between the area of oil palm plantations and oil palm production in Indonesia, especially in the Sumatra and Kalimantan regions which are the centers of oil palm plantation distribution. Data collection using secondary data from the Central Statistics Agency (BPS), this study aims to determine the relationship between the increase in land area and oil palm plantation production over the past 10 years. This study uses a quantitative method with a correlative approach. Data analysis was carried out using a bivariate correlation Pearson correlation test to determine the positive relationship between plantation area and oil palm production. The results of the analysis showed a significant positive relationship between the land area variable and oil palm production in both the Sumatra and Kalimantan regions, this is indicated by a positive number and a strong correlation of 0.852 for the Sumatra region and very strong, namely 0.996 for the Kalimantan region. In addition, the results of the interpretation of the correlation by looking at Sig. (2-tailed) also show that between the land area variable and production there is a significant correlation, namely 0.002 for the Sumatra region and a value of 0.000 for the Kalimantan region. Although the correlation between land area and production shows a positive value and has a very strong correlation, there are still other factors such as technology, climate, and management practices that also play a role in influencing palm oil production results.